2022
DOI: 10.1108/ijlma-06-2021-0154
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of accounting students’ attitudes toward integrating forensic accounting in accounting education

Abstract: Purpose Because of the increasing number of corruption and financial fraud cases, especially in developing countries, the education of forensic accounting has become important and universities should offer it as part of its curriculum. This study aims to explore the current status of forensic accounting education in Saudi Arabia as a developing country and its adequacy from the perspectives of accounting students in Saudi universities. Design/methodology/approach A questionnaire survey was administered to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…This confirms the second hypothesis of the study, stating that stakeholders have different perceptions regarding the challenges of incorporating forensic accounting education into the accounting curricula in Jordan. Additionally, these results align with previous research in the field, such as Ebaid (2022), Prabowo (2021) and Rezaee and Wang (2022).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This confirms the second hypothesis of the study, stating that stakeholders have different perceptions regarding the challenges of incorporating forensic accounting education into the accounting curricula in Jordan. Additionally, these results align with previous research in the field, such as Ebaid (2022), Prabowo (2021) and Rezaee and Wang (2022).…”
Section: Resultssupporting
confidence: 91%
“…Previous research studies have confirmed similar results such as those conducted by Akinbowale et al . (2021), Ebaid (2022), Prabowo (2021), Rezaee and Wang (2022) and Van Akkeren and Tarr (2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraudulent actions trigger financial catastrophes with far-reaching economic consequences, such as the collapse of financial institutions and other large corporations. Several problems in Saudi Arabia's (KSA) forensic accounting curriculum must be addressed (Ebaid, 2022; Senan and Swalih, 2019). In particular, instead of a short training course, the accounting curriculum for undergraduate and postgraduate study needs to be revised (Albader, 2015).…”
Section: Introductionmentioning
confidence: 99%